2009
DOI: 10.1590/s0102-311x2009000100006
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders and chronic non-communicable diseases in adults: a population-based study

Abstract: A cross-sectional population-based study was conducted to identify the prevalence of common mental disorders and verify the association with chronic non-communicable diseases (NCDs) and the self-reported number of chronic diseases. The IntroductionIn recent decades, studies in psychiatric epidemiology have provided valuable information leading to better knowledge of the natural history of mental disorders and the identification of groups at increased risk, thus forming the basis for policy and treatment dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1
19

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 22 publications
5
15
1
19
Order By: Relevance
“…Such prevalences are higher than those detected in a previous study among carriers of noncommunicable chronic diseases (major depressive disorder, 17.6%; generalized anxiety disorder, 11.5%; dysthymia, 11.3%) using the Structured Clinical Interview for DSM Disorders (SCID-IV-TR). 23 Similar to our results, a study conducted in a population from the Family Health Program using the Composite International Diagnostic Interview (CIDI) detected a median of three psychiatric diagnoses per patient; 56% had common mental disorders (anxiety, 40%, depressive disorders 45%) and 11% had mental disorders due to alcohol use. 24 In the present study, the odds of alcohol and/or psychoactive substance abuse/dependence were higher among individuals living with HIV/AIDS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Such prevalences are higher than those detected in a previous study among carriers of noncommunicable chronic diseases (major depressive disorder, 17.6%; generalized anxiety disorder, 11.5%; dysthymia, 11.3%) using the Structured Clinical Interview for DSM Disorders (SCID-IV-TR). 23 Similar to our results, a study conducted in a population from the Family Health Program using the Composite International Diagnostic Interview (CIDI) detected a median of three psychiatric diagnoses per patient; 56% had common mental disorders (anxiety, 40%, depressive disorders 45%) and 11% had mental disorders due to alcohol use. 24 In the present study, the odds of alcohol and/or psychoactive substance abuse/dependence were higher among individuals living with HIV/AIDS.…”
Section: Discussionsupporting
confidence: 89%
“…25 The detected association between family income below two minimum wages and excessive alcohol/drug abuse strengthens the association between socioeconomic status and occurrence of mental disorders in a population of individuals with chronic disease, as previously suggested in a review article 26 covering the period of 1997-2009 and in two Brazilian studies that identified an overall prevalence of mental disorders of 36% in individuals with a per capita income below 50 Brazilian reais 27 and of 30.2% in unemployed individuals with low educational attainment. 23 Current frequency of suicide risk (past month) was high (56.8%) in this population, associated with unemployment, non-white skin color, and diagnosis of major depression, which is more concerning considering that suicidal behaviors are known to be associated with HIV infection 28,29 and that this risk is higher among those with a prior history of suicide attempt 30 and in those with social and psychological stressors, such as unemployment or having an HIV-positive partner. 29 Despite the lack of consensus and the different methods for data collection on suicide, several studies have investigated the prevalence of suicidal ideation and suicide attempt in HIV-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Outros autores têm observado esses gradientes e verificado que a prevalência de transtorno mental comum é cerca de 4 vezes maior de idosos com 4 a 5 morbidades relativamente aos que não apresentavam doenças crô-nicas 43,44 . As doenças crônicas, frequentemente encontradas nos idosos, associam-se à incapacidade funcional 45,46 , a aumento da vulnerabilidade e da dependência, contribuindo para o isolamento social e podendo, por conseguinte, aumentar a presença de sintomas somáticos, depressivos e ansiosos, entre outros 47 .…”
Section: Discussionunclassified
“…O instrumento é composto por 20 questões, sendo as 4 primeiras relacionadas a sintomas físicos e outras 16 sobre sintomas psicoemocionais 16,17 .…”
Section: Instrumentos E Variáveis Coletadasunclassified
“…É altamente recomendado para estudos de bases populacionais, especialmente em grupos de trabalhadores, tendo em vista a associação dos sinais e sintomas com a diminuição das funções laborais e sociais 16,17 .…”
Section: Instrumentos E Variáveis Coletadasunclassified